2013
DOI: 10.1007/s00264-013-2008-0
|View full text |Cite
|
Sign up to set email alerts
|

Acetabular cup positioning in revision total hip arthroplasty with Paprosky type III acetabular defects: Martell radiographic analysis

Abstract: Purpose This study evaluates acetabular cup position in the setting of revision total hip arthroplasty (THA) with severe acetabular bone defects. Methods With a definition of safe zone of abduction (30-50°) and anteversion (5-25°), acetabular cup position was measured by a digital image analysis program for 34 patients with Paprosky type III acetabular bone defects. Results There were 24 cups (71 %) for abduction and 26 cups (76 %) for anteversion located in the safe zone. Nineteen cups (56 %) were within the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 27 publications
2
17
0
Order By: Relevance
“…However, they used different methods of reconstruction in their study. 18 In our study, only three of 16 patients did not meet the parameters of Lewinnek's safe zone. The safe zone, as such, was not the main goal, because normal acetabular anatomy should not be expected, nor should it be assumed that the average position of the acetabular component is ideal for every patient 11 and Goudie et al 19 found natural acetabular orientation in arthritic hips outside of the safe zone of Lewinnek in up to 75% of hips.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…However, they used different methods of reconstruction in their study. 18 In our study, only three of 16 patients did not meet the parameters of Lewinnek's safe zone. The safe zone, as such, was not the main goal, because normal acetabular anatomy should not be expected, nor should it be assumed that the average position of the acetabular component is ideal for every patient 11 and Goudie et al 19 found natural acetabular orientation in arthritic hips outside of the safe zone of Lewinnek in up to 75% of hips.…”
Section: Discussionmentioning
confidence: 51%
“…Others have found satisfactory alignment of acetabular components at primary THA performed with the patient supine which is a difficult position for revision THA. 17 Choi et al 18 reported that freehand positioning of the acetabular component can be inaccurate at revision THA in patients with Paprosky type 3 defects: in their series only 19 of 34 components (56%) were positioned within the safe zone of Lewinnek. However, they used different methods of reconstruction in their study.…”
Section: Discussionmentioning
confidence: 96%
“…Concerns of a high dislocation rate following revision hip procedures are justified. Optimal cup placement into the safe zone during acetabular revision for severe bone loss is difficult to obtain [30]; therefore, supplemental cup reorientation with a modular acetabular prosthesis is advantageous. The only late dislocation in our study was revised due to femoral revision stem subsidence.…”
Section: Discussionmentioning
confidence: 99%
“…Small contained defects can usually be treated with porous hemispherical cups with supplemental bone grafting [6]. However, large uncontained lesions often require extralarge hemispherical cups, impaction grafting, structural allografts, bilobed oblong cups or anti-protrusio rings and reconstruction cages [7][8][9][10][11][12][13][14][15][16]. Although the results of cementless fixation appears to be satisfactory in many revision scenarios, less satisfactory outcomes have been reported in some studies when less than 50 % of the weight bearing host bone is available for fixation, which may lead to failure of biological ingrowth [17].…”
Section: Introductionmentioning
confidence: 99%